1형당뇨병 예방 약물의 현재와 미래: 테플리주맙과 면역조절약물 - 손희석; 김수종; 윤정현 (한국임상약학회지, 2024)
Type 1 diabetes (T1D) is a chronic autoimmune disease characterized by the destruction of insulin-producing beta-cells in the pancreas. Genetic variations within the major histocompatibility complex (MHC) significantly influence the development of T1D, with disease progression often indicated by the presence of autoantibodies. Until recently, insulin therapy was the sole treatment for T1D. However, in 2022, the Food and Drug Administration approved teplizumab, an anti-CD3 monoclonal antibody, as a novel immunomodulatory therapy to delay the onset of T1D. Various immunologic agents, including anti-CD antibodies and anti-cytokine autoantibodies, have been investigated across various stages of T1D in clinical trials. This article examines the current status of drug development for the prevention and treatment of T1D and summarizes key studies that aimed at delaying the onset of T1D using these agents. While efforts to halt or prevent the disease prior to clinical diagnosis have yielded limited success, post-diagnosis interventions have shown promising potential in slowing disease progression by preserving beta-cell function. Further investigation into long-term clinical outcomes related to the delay of T1D onset is necessary, and ongoing studies require extended follow-up to assess their full potential.